-2(3t-4)+3t=2t-3

Simple and best practice solution for -2(3t-4)+3t=2t-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3t-4)+3t=2t-3 equation:


Simplifying
-2(3t + -4) + 3t = 2t + -3

Reorder the terms:
-2(-4 + 3t) + 3t = 2t + -3
(-4 * -2 + 3t * -2) + 3t = 2t + -3
(8 + -6t) + 3t = 2t + -3

Combine like terms: -6t + 3t = -3t
8 + -3t = 2t + -3

Reorder the terms:
8 + -3t = -3 + 2t

Solving
8 + -3t = -3 + 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
8 + -3t + -2t = -3 + 2t + -2t

Combine like terms: -3t + -2t = -5t
8 + -5t = -3 + 2t + -2t

Combine like terms: 2t + -2t = 0
8 + -5t = -3 + 0
8 + -5t = -3

Add '-8' to each side of the equation.
8 + -8 + -5t = -3 + -8

Combine like terms: 8 + -8 = 0
0 + -5t = -3 + -8
-5t = -3 + -8

Combine like terms: -3 + -8 = -11
-5t = -11

Divide each side by '-5'.
t = 2.2

Simplifying
t = 2.2

See similar equations:

| -27x^3+48x-5= | | 10x^2+2.5x-45=0 | | 3x+11=6x-4 | | 5+6=5+x | | 6x^2-4x=-11 | | 8+y=6+2y | | -5(3t-2)+2t=4t-9 | | x^4-8x^3+98x^2-648x+1377=0 | | 36m^-4n^-6/4mn^-2p^-4 | | -x^2-100=0 | | 19=4-2m-m+7 | | (2x+4)+(3x-13)=180 | | 20a+25= | | 12-4y=2(y+9) | | 2.50x=500+0.35x | | 16a+28= | | 150x+50y=8395 | | (2a/a^2)^-2 | | 50(x+5)=a | | 200x+100y=12995 | | 3k(3k+10)=0 | | (2a/a^2)^2 | | 5x-2x=x+30 | | 3x-2=5x-19 | | 1-x=-9 | | 12a+8b= | | 7/8(16) | | 8x-4=-10x-3 | | 6(x-9)=24 | | 12x+5y=24547 | | 36w^2+39w+75=-2w-4 | | 1-6r=4-3r |

Equations solver categories